Comparison of Rosuvastatin Versus Atorvastatin on Lipid Lowering Effectiveness in Hyperlipidemic Patients - Usama Atiq, Rameen Rafique, Fahd Karamat Baig, Arslan Murtaza, Sami Atiq, Eesha Tehreem, (Pakistan Journal of Medical & Health Sciences, 2022)
Hyperlipidaemia is the utmost important factors influencing coronary heart disease. Statins are supposed to be the 1st line of drug in clinical exercise for lowering low-density lipoprotein, total cholesterol and increasing HDL cholesterol. This study was held for the comparison of the safety and efficacy of atorvastatin and rosuvastatin in lowering hyperlipidaemia among hyperlipidemic patients. Study Design: A prospective observational study. Place and Duration: In the Medicine department of Mayo hospital, Lahore for three-months duration from 15th March 2021 to 15th June 2021. Methods: This study comprised 90 patients with newly diagnosed hyperlipidaemia divided into two groups containing equal number of patients in both. Patients prescribed 10 mg of atorvastatin in Group A and 5 mg of rosuvastatin in Group B once daily for 6 weeks by the treating doctor of medicine. The data was saved in a personalized proforma format, and the SPSS 20.0 was used for analysis. Results: Serum total cholesterol decreased significantly afterwards the treatment with the rosuvastatin and atorvastatin groups (p <0.00001, correspondingly), but no significant variance (p = 0.510) noticed among the both groups treated with statins. The decrease in serum triglycerides was also significant (p = 0.0006 in the rosuvastatin group and p = 0.042 in the atorvastatin group) but the comparable difference in lowering hyperlipidemia was no significant among the both groups (p = 0.309). Similarly, LDL-C serum levels were significantly reduced in both groups (p <0.00001) but no statistically significant variance (p = 0.756) noticed among the two groups in terms of efficacy. Conclusion: No substantial changes in serum HDL levels were observed. The difference among the both groups was not significant (p = 0.731). This analysis = shows that both rosuvastatin and atorvastatin improved the lipid profile, but no changes were seen significantly among the both groups.